인공시효 온도가 자연시효된 Al-Si-Mg 합금의 T6 거동에 미치는 영향 - 손현우; Hyeon-woo Son; 정재은; Jae-eun Jeong; 조영희; Young-hee Cho; 김수배; Soo-bae Kim; 이정무; Jung-moo Lee (대한금속·재료학회지, 63(3), 2025)
The artificial aging behavior of Al-Si-Mg alloy naturally aged for 1 hour and 7 days at room temperature was analyzed using hardness, DSC and TEM. The Al-Si-Mg alloy naturally aged for 7 days at room temperature showed a decrease in maximum hardness during artificial aging at 160℃ compared to the 1-hour natural aging condition. However, at an artificial aging temperature of 180℃, the reduction in hardness due to natural aging was insignificant. The DSC analysis of naturally aged and artificially aged samples showed that at 160℃ artificial aging temperature, the temperature range of the exothermic peak due to β″ and β′ formation and the enthalpy of reaction decreased with increasing aging time. However, at a temperature of 180℃, there was no deviation in the DSC analysis results according to natural aging. The distribution of clusters and precipitates according to the natural aging time showed a significant deviation at the artificial aging temperature of 160℃, while it did not show a significant deviation at the artificial aging temperature of 180℃. The high artificial aging temperature was analyzed to minimize the negative effects of natural aging by rapidly dissolving the clusters (1) formed during natural aging early in the aging process. It is believed that a multi-stage aging process including high temperature artificial aging can be developed to eliminate the natural aging effect and improve the mechanical properties of Al- Si-Mg alloys.